2008
DOI: 10.1242/dmm.000463
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy for the diseased liver: from stem cell biology to novel models for hepatotropic human pathogens

Abstract: It has long been known that hepatocytes possess the potential to replicate through many cell generations because regeneration can be achieved in rodents after serial two-thirds hepatectomy. It has taken considerable time and effort to harness this potential, with liver regeneration models involving hepatocyte transplantation developing over the past 15 years. This review will describe the experiments that have established the models and methodology for liver repopulation, and the use of cells other than adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…Humanized mice bearing chimeric human livers represent an important tool to study human hepatotropic infections [ 8 , 9 ]. Liver toxicity generated by hepatocyte-specific expression of the urokinase plasminogen activator (uPA) transgene creates a ‘niche’ for growth of adoptively transferred hepatocytes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humanized mice bearing chimeric human livers represent an important tool to study human hepatotropic infections [ 8 , 9 ]. Liver toxicity generated by hepatocyte-specific expression of the urokinase plasminogen activator (uPA) transgene creates a ‘niche’ for growth of adoptively transferred hepatocytes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the potential of stem cells or isolated HSPCs to rescue a damaged liver when HSPCs have an advantage over damaged hepatocytes in mouse models such as the uPA/SCID and FAH or FRG mouse models (Brezillon et al, 2008[ 8 ]; Grompe et al, 2013[ 30 ]) (Figure 2 (Fig. 2) ).…”
Section: Participation Of Endogenous Hspcs In Liver Repairmentioning
confidence: 99%
“…The liver tissue mass can be restored after two-thirds hepatectomy, as shown by Higgins and Anderson in the 1930s in rat models. 36 The human liver also contains a population of stem cells as well as bipotential oval cells that can differentiate into hepatocytes when necessary. 37,38 Unfortunately, in severe liver diseases, the hepatocytes' and the liver stem cells' regenerative capacity may be impaired.…”
Section: Gpscs and Liver Regenerationmentioning
confidence: 99%